The social, economic, and environmental implications of biomass ethanol production in China: A multi-regional input-output-based hybrid LCA model. (10th March 2020) - Wang, Changbo; Malik, Arunima; Wang, Yafei; Chang, Yuan; Lenzen, Manfred; Zhou, Dequn; Pang, Mingyue; Huang, Qingxu
Abstract: As an alternative to conventional liquid fuels, bioethanol holds the promise of transitioning to a clean and low-carbon energy future. China's bioethanol industry is at its nascent stage. In this study, we developed a hybrid life cycle assessment model that integrates the multi-regional input-output (MRIO) approach and specific production data to evaluate the social, economic, and environmental (i.e. the triple-bottom-line, TBL) impacts of the bioethanol sector in China's economic systems. The MRIO model was constructed using the 2012 MRIO table, and the data for the typical technologies of bioethanol production were leveraged. To be specific, we evaluated employment creation, economic stimulus, and energy use of bioethanol production in 28 scenarios in Henan province. The results show that compared to petroleum refining, bioethanol production is more effective for economic stimulus and energy saving, but less effective at job creation. The impact of bioethanol production varies by technologies. For every 1 million yuan of bioethanol production in China' economic system, first-generation technology offers a projected 1.92 million yuan in economic growth and job creation of 2.06 full-time equivalent, while the second-generation technology offers a lower energy consumption (1.19 TJ). In most scenarios, the upstream sectors account for more than half of the TBL impacts of biofuel production. This study helps to quantify the TBL impacts associated with the gasoline-to-bioethanol transition in China, envisions the green opportunities for impact mitigation, and sheds light on the potential direction for robust planning and policy making to advance the bioethanol industry's development. Highlights: A MRIO-based hybrid LCA was undertaken for bioethanol production in China. Employment, economic stimulus and energy use were assessed for bioethanol production. Bioethanol is more effective on energy saving and economic stimulus than gasoline. Second-generation bioethanol has the highest energy return on investment value. Supply-chain sectors make up the majority of social and environmental impacts.